Analyzing the Content of the Chemistry Book for the Fifth Grade of Preparatory School According to Imaginative Thinking Skills (Journal Of Educational and Psychological Researches, 2022)
The aim of the research is to identify the imaginative thinking skills included in the content of the chemistry textbook for fifth-grade students in biological sciences at the preparatory stage, which is approved by the Ministry of Education, General Directorate of Curricula in the academic year 2020-2021. To achieve the objective of the study, the researcher depends on the previous studies in the field and content of imaginative thinking skills for preparing a list of skills that includes (3) essential skills and (11) sub-skills and (28) items related to all skills. The researcher adopted the analytical descriptive approach because of its appropriation of the goals of the research. Then the researcher analyzed the content of the book depending on the unity of the idea as a unit to registration and repetitions and as a unit to enumeration. The results found that the chemistry book for the fifth scientific class for the preparatory stage achieved (2002) repetitions at a rate (30%) Of imaginative thinking skills included in the book of chemistry. According to these results, the researcher set a number of recommendations: giving more attention to the neglected imaginative thinking skill and it included them in the syllabus of chemistry for the fifth scientific class (the preparatory stage). Providing modern technology means and their applications in the schools as a means to attract student`s attention to raise their level of education. Analyzing chemistry textbooks for all other stages based on the skills of imaginative thinking skills.